UPAYA GREENPEACE DALAM MENGATASI LIMBAH BERACUN DI TIONGKOK - M Rahmat Sya’ar; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This is a contemporary study that provides an analysis of the deal with toxic waste in China through the implementation of Greenpeace as an international organization with programs Detox Campaign.This paper uses the conceptual underpinnings, by applying the concept of the role of the implementation of the program to see how big an impact in tackling the toxic waste in China by focusing on a specific area. Powered by role theory, pluralist perspective and analysis of the level of international organizations, as well as the concept of environmentalism. The concept leads to a qualitative method and the study of literature as a source of information.Some Greenpeace efforts in addressing the above problems is the core strategy of advocacy, monitoring, research, communication and evaluation of the river, namely: Yangtze river is located in Ningbo Province, the Pearl River which bearada in Zhongshan province. So far these efforts give good results against the Chinese government as well as public awareness for good behavior change towards the environment. ,Keywords: Greenpeace, program, toxic waste